2023
DOI: 10.17586/2687-0568-2023-5-2-56-76
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide for Hydrogen Economy: a Brief Review

Abstract: Our research is mainly focused on solving problems related to the production of hydrogen and its storage, as well as the creation of autonomous energy systems using renewable energy sources. Technological solutions for green energy depend on the development of new materials with desired properties that are able to reversibly accumulate hydrogen under appropriate environmental conditions (temperature, pressure) and on the technological processes allowing to obtain molecular hydrogen without significant energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 137 publications
(162 reference statements)
0
0
0
Order By: Relevance
“…It is observed that the darker the color, the higher the ability to absorb light, so "black TiO2" shows the highest intensity of visible light absorption. Nanomaterials based on TiO2 and especially "black" are of great interest for photocatalytic hydrogen production using solar energy [13]. It is noted that "gray" titanium leads to the formation of peculiar defective catalytic centers, which make it possible to generate hydrogen without co-catalysts (usually Pt and other noble metals).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the darker the color, the higher the ability to absorb light, so "black TiO2" shows the highest intensity of visible light absorption. Nanomaterials based on TiO2 and especially "black" are of great interest for photocatalytic hydrogen production using solar energy [13]. It is noted that "gray" titanium leads to the formation of peculiar defective catalytic centers, which make it possible to generate hydrogen without co-catalysts (usually Pt and other noble metals).…”
Section: Introductionmentioning
confidence: 99%